2004
DOI: 10.1111/j.1365-2249.2003.02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of innate immunity by susceptible and multidrug-resistant Pseudomonas aeruginosa: an in vitro and in vivo study

Abstract: SUMMARYIn attempt to investigate the stimulatory effect of Pseudomonas aeruginosa on innate immunity and to correlate it to its level of resistance to antimicrobials, 20 isolates were applied; 8 isolates were susceptible and 12 multidrug-resistant. Genetic diversity was defined by PFGE. Human monocytes of two healthy volunteers were in vitro stimulated by the isolates for the production of pro-inflammatory (TNF-a , IL-1 b , IL-6, IL-8 and IL-12) and anti-inflammatory cytokines (IL-10), of malondialdehyde and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 16 publications
7
23
0
2
Order By: Relevance
“…These findings may be consistent with in vitro ev- idence showing that resistance genes or mutations can alter the fitness of microorganisms (4), making them less virulent and reducing their capacity to generate deleterious host inflammatory responses (22). Nevertheless, the complex interplay between resistance mechanisms, cost-compensatory mutations, fitness, and virulence in the clinical setting has yet to be fully elucidated (1).…”
Section: Discussionsupporting
confidence: 75%
“…These findings may be consistent with in vitro ev- idence showing that resistance genes or mutations can alter the fitness of microorganisms (4), making them less virulent and reducing their capacity to generate deleterious host inflammatory responses (22). Nevertheless, the complex interplay between resistance mechanisms, cost-compensatory mutations, fitness, and virulence in the clinical setting has yet to be fully elucidated (1).…”
Section: Discussionsupporting
confidence: 75%
“…Several attempts to correlate resistance and individual isolate characteristics to virulence and immune system stimulation have been made in the past. Giamarellos-Bourboulis et al (15) demonstrated that significant differences are encountered in host-pathogen interactions between MDR and susceptible Pseudomonas aeruginosa isolates; susceptible isolates induced a greater release of proinflammatory cytokines accompanied by increased mortality in rodents. The opposite was found when the study design was repeated with E. coli species.…”
Section: Discussionmentioning
confidence: 99%
“…No analgesics were used, as the operation was brief. A 2 cm-long midline incision was made on the neck to expose the right inner jugular vein [8,9]. An 18G catheter was inserted and 1 × 10 8 colony forming units (cfu) per kg of the prepared K. pneumoniae isolate was injected, in a volume of 2.0 mL.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…Some studies have concluded that patients infected with bacteria susceptible to drug treatment had a better outcome than did patients infected with multidrug-resistant bacteria [6,7]. Other studies by Giamarellos-Bourboulis and Bristianou showed that rabbits infected with drug susceptible strains of E. coli had worse outcomes than those infected with multidrug-resistant strains, and cytokine release patterns were di erent [8][9][10]. Glauser suggested that multidrug-resistant isolates might interfere with the mechanism leading to sepsis, resulting in lower pathogenicity [11].…”
mentioning
confidence: 99%